2016
DOI: 10.1590/0001-3765201620150009
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of annual growth rings in Rhizophora mangle in a region with low climate seasonality

Abstract: The formation of annual growth rings has been confi rmed for several mangrove species in the last decade, among which is the Rhizophora mangle. However, the record of annual rings for this species was made in a region with high hydric seasonality, a widely recognized induction factor of annual rings in tropical species. In this sense, the present study aimed to verify the occurrence of annual growth rings in R. mangle in the mangroves of Guaratiba (Rio de Janeiro, Southeastern Brazil), a region with low hydric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…In fact, both species showed similar growth-climate responses, resulting in positive correlations between chronologies over their lifespan. It is interesting that most native species in the Atlantic Forest environment show positive correlations between growth of the trees and precipitation of the current growing season (Latorraca et al 2015;Souza et al 2016;Fontana et al 2018;Aragão et al 2019). Moisture-sensitive tree species tend to grow and accumulate nutrients during the rainy season (Fritts 1976;Dünisch et al 2003;Kunert et al 2010) between September and April in the study area ( Fig.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, both species showed similar growth-climate responses, resulting in positive correlations between chronologies over their lifespan. It is interesting that most native species in the Atlantic Forest environment show positive correlations between growth of the trees and precipitation of the current growing season (Latorraca et al 2015;Souza et al 2016;Fontana et al 2018;Aragão et al 2019). Moisture-sensitive tree species tend to grow and accumulate nutrients during the rainy season (Fritts 1976;Dünisch et al 2003;Kunert et al 2010) between September and April in the study area ( Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Todas as características ora descritas foram observadas em R. mangle por Record & Hess (1949), Détienne & Jacquet (1983), Richter & Dallwitz (2009) e Melo Junior et al (2016, exceto a distribuição dos poros, descrita pelos autores como difusa. Fibras libriformes não septadas com pontoações simples caracterizam o tecido de sustentação desta espécie, condizendo com o material de R. mangle descrito por Souza et al (2016). Plaziat (1995) destaca que a identificação de antigas comunidades de vegetação de mangue pode ser realizada por meio de marcadores biológicos, como grãos de pólen, frutos e estruturas de madeira preservadas nos sedimentos, enfatizando, ainda, que as raízes, juntamente com impressões de pneumatóforos, são indicadores de populações pretéritas de manguezais.…”
Section: Resultsunclassified
“…A estrutura lenhosa estudada apresenta camadas de crescimento distintas, individualizadas por anéis semiporosos e pelo espessamento transversal das paredes das fibras (Figura 3A). Apesar de Record & Hess (1949), Détienne & Jacquet (1983) e Richter & Dallwitz (2009) considerarem que tais camadas para a espécie R. mangle, em sua maioria, sejam usualmente indistintas ou pouco distintas, neste trabalho, foram observadas camadas bem definidas, semelhantes às verificadas por Souza et al (2016), que, baseando-se na ocorrência desta espécie no município de Guaratiba, Rio de Janeiro, observaram camadas de crescimento distintas, demarcadas por poros de menor diâmetro no lenho tardio e pela densidade elevada nesta região.…”
Section: Resultsunclassified
“…Dendrochronological studies developed in the Amazonian floodplains also showed a negative correlation between ring width and the amount of precipitation and flood pulse during the vegetation period (Schongart et al 2004). In Brazil, with the exception of the ecosystems investigated by Schongart et al (2004), other studies in tropical climate showed strong influence of precipitation in the radial growth (Callado & Guimarães 2010;Brandes et al 2011;Latorraca et al 2015;Locosselli et al 2016b;Souza et al 2016;Granato-Souza et al 2019;Vasconcellos et al 2019), whereas negative correlations are more often in subtropical climate (Oliveira et al 2010;Andreacci & Botosso 2014;Perone et al 2016;Kanieski 2017;Granato-Souza et al 2018a;b). As in L. bahiana, a study carried out with Chukrasia tabularis A. Juss.…”
Section: Dendrochronologymentioning
confidence: 96%